"Make it beautiful". An old request with difficult academic answers. (28th July 2017) - Ferraris, Silvia D.; Rampino, Lucia; Ferraro, Venere
Abstract: The evolution of Design as a discipline witnessed a controversial attitude towards the role of aesthetics in the work of designers. Following the functional creed, in many technical academic entourages evolved the idea that a designer job is anything but developing an aesthetic language. In the meantime, in the not-academic world, outsiders think that Design is largely about "making things beautiful". Based on these grounds, the authors have in recent past years started to teach their students to consider the aesthetics of their design by reflecting on the form-giving issue. To introduce it smoothly into a technical university environment, they choose to avoid words such as "beautiful" or "attractive", rather they speak of "language of products" and of making products "recognizable". The authors apply this approach in their teaching through the development of specific exercises and tools. In this article, the overall meaning of this kind of experience is discussed to highlight faults and possible further developments in the perspective of an ever-evolving design discipline.